2017
DOI: 10.1097/md.0000000000007735
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplantation anemia in kidney transplant recipients

Abstract: We sought to assess the frequency and predictors of early and late posttransplantation anemia (PTA). In addition, we aimed to assess the outcomes of patients with anemia and to assess the impact of anemia on mortality, graft function, and graft failure.Patients who underwent kidney transplantation in a single center during a 4-year period were included. Predictors associated with the development of anemia at 6 months (early PTA) or 2 years (late PTA) were evaluated in a univariate and multivariate analyses. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 49 publications
2
28
0
1
Order By: Relevance
“…In our study, anemia was diagnosed in 36% of the cohort, in agreement with previous studies which showed a late PTA prevalence of 20–40% [16, 23, 27, 37, 38, 42, 44].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, anemia was diagnosed in 36% of the cohort, in agreement with previous studies which showed a late PTA prevalence of 20–40% [16, 23, 27, 37, 38, 42, 44].…”
Section: Discussionsupporting
confidence: 93%
“…PTA has previously been shown to be associated with the composite outcome of all-cause mortality and graft loss [6, 17, 18, 27, 3739], as well as the separate components: death-censored graft survival [4, 19, 20] and all-cause mortality [6, 1518]. However, the association between PTA and increased mortality is inconsistent, as several studies failed to show association with all-cause mortality, despite an association with graft loss [4, 19, 40–43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anemia prevalence decreases following kidney transplant, from 71% pre-transplant to 51% at 6 months and 37% at 2 years post-transplant. However, post-transplant anemia does occur [ 78 ]. In kidney transplant recipients, lower Hb is a predictor for a return to dialysis, graft failure, subsequent kidney transplant, reduced LV mass index, or death [ 78 , 79 ].…”
Section: Special Populationsmentioning
confidence: 99%